Integrated modeling and its potential for resolving conflicts between conservation and people in the rangelands of East Africa - Galvin, K.A.; Thornton, Philip K.; Pinho, J.R. de; Sunderland, J.; Boone, Randall B. (Springer, 2006)
A major challenge for contemporary conservation policies and practices is formulating workable compromises between wildlife conservation and the people who live with wildlife. We strongly support the view that anthropology has a critical role to play in contributing to our understanding of human-environment interactions. The study of complex biophysical and human systems can be greatly assisted by appropriate simulation models that integrate what is known about ecological and human decision-making processes. We have developed an integrated modeling system for assessing scenarios in the Ngorongoro Conservation Area in northern Tanzania to modify the situation there to improve human welfare without compromising conservation value. We present the results of some scenarios that indicate that the current situation there is not sustainable, and that tough policy decisions need to be taken if household well-being of the pastoralists who live there is to be improved or even sustained.